2011
DOI: 10.1186/1471-2458-11-194
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of screening for high blood pressure in dental health care

Abstract: BackgroundThere is consensus on the importance of early detection and treatment of high blood pressure. Dental care is one of few medical services to which a considerable proportion of the general population comes for regular check-ups. We tested the effects of blood pressure screening in dental care centres with subsequent work-up of subjects screening positive in primary health care (PHCC).MethodsAltogether 1,149 subjects 40-65 years old or 20-39 years old with body mass index >25, and with no previously kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 13 publications
1
36
1
1
Order By: Relevance
“…9 A British study found that few dentists screened for high blood pressure, although more than 25% felt it was a good idea. 10 Early detection of the chronic condition can save more than 75% of the total cost of the treatment and decrease the chance of causing deaths by 70%. 9 According to the medical expenditure panel survey, only 10 to 20% of the adults have seen physician yearly, whereas about 40% of the adults visit the dentist on a yearly basis.…”
Section: Introductionmentioning
confidence: 99%
“…9 A British study found that few dentists screened for high blood pressure, although more than 25% felt it was a good idea. 10 Early detection of the chronic condition can save more than 75% of the total cost of the treatment and decrease the chance of causing deaths by 70%. 9 According to the medical expenditure panel survey, only 10 to 20% of the adults have seen physician yearly, whereas about 40% of the adults visit the dentist on a yearly basis.…”
Section: Introductionmentioning
confidence: 99%
“…4,6 Systemic considerations by dentists can be valuable additions to improving the nations' health, particularly in detecting asymptomatic conditions. 7 One example is Engström et al, 8 who excellently demonstrated the value of screening for hypertension in Sweden, and there seems to be no real reason why this effect could not be duplicated in the UK.…”
Section: Systemic Health Screeningmentioning
confidence: 99%
“…Even though hypertension is the most commonly diagnosed disease worldwide, undiagnosed hypertension is still prevalent in various patient populations. The findings of one study concluded that 20% of the sample patient population examined had undiagnosed hypertension [3]. Therefore, the clinician has an important role in screening for hypertension.…”
Section: Medical Historymentioning
confidence: 99%